An Analysis of Cloud Computing and Future Benefits (International Journal of Food and Nutritional Sciences, 2022)
The phrase cloud computing refers to the online storage and accessibility of data. It does not save any information on your computer's hard drive. Users can get information from a remote server by using cloud computing. This essay briefly covers the development, background, and nomenclature of cloud computing. Although cloud computing is not a new technology, it is now one of the fastest technological advancements due to its powerful and significant impact on how data or services are managed. This paper examines the characteristics, service model, deployment patterns, and origins of cloud computing, in addition to discussing its development, background, and definition. Cloud Environment Private Cloud Model for the public cloud. In this paper, the author talks about cloud computing and its benefits. In the future, this paper will make people aware of the benefits of cloud computing or cloud computing.